Impact of patient aggression and violence against physicians on the team and organisational levels in China: a qualitative study - Kees Ahaus; Martina Buljac-Samardžić; Yuhan Wu; Dahai Zhao (BMJ Open)
Objectives Aggression and violence against physicians in hospitals is acknowledged to be an issue, and patients (and their relatives/friends) have been identified as the most prevalent source. The aim of this study is to investigate the impact of patient aggression and violence against physicians on the team and organisational levels.Design This is a qualitative interview study based on semistructured, in-depth individual interviews. Interview transcripts were coded and analysed in Atlas.ti.Setting Interviews were conducted in Chinese hospitals.Participants This study involved 29 diverse participants, including physicians, hospital team leaders and hospital board members, working in two secondary hospitals and two tertiary hospitals in China.Results This study found that, at the team level, aggression and violence by patients (and their relatives/friends) can affect team climate, team communication, team beliefs and team resources. At the organisational level, such aggression and violence can have negative financial impacts (ie, involving compensation and additional costs) and societal impacts (ie, image and reputational damage, and public distrust). Although peer support and leaders’ support were identified as important sources for physicians to deal with violent incidents, these sources were not used to their full potential.Conclusions Recovering a team climate after a violent incident and providing diverse forms of support, especially proactive support from leaders and peers, represent two important approaches to cope with the negative impact of patient (and their relatives/friends) aggression and violence against physicians on both team and organisational levels.